2010
DOI: 10.1097/phm.0b013e3181d8a5b1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repetitive Transcranial Magnetic Stimulation on Cognition and Mood in Stroke Patients

Abstract: These preliminary data suggest that there was a positive effect on mood, but the study was not powered to detect any measurable effect on cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(138 citation statements)
references
References 18 publications
3
130
1
4
Order By: Relevance
“…We suspect that heterogeneity of etiologies would cause a minor effect on our results. Finally, we defined the MT as the minimal intensity to achieve an MEP of at least 100 µV as Kim et al,26 and this was higher than that of most previous studies, which used 50 µV. We also used a circular coil to measure MEPs, and a figure-eight coil for rTMS.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that heterogeneity of etiologies would cause a minor effect on our results. Finally, we defined the MT as the minimal intensity to achieve an MEP of at least 100 µV as Kim et al,26 and this was higher than that of most previous studies, which used 50 µV. We also used a circular coil to measure MEPs, and a figure-eight coil for rTMS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed positive results of treatment with citalopram (51), but there were very frequent adverse effects. The stroke randomized trials by Kim et al (52) and Jorge et al (53) enrolled 18 and 20 patients, respectively, using rTMS over the left DLPFC. Both observed improvement of depression symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Исследование факторов, регулирующих гиппокампальный нейро-генез у взрослых, породило крупное научное поле деятельности в этом направлении, и ряд открытий имел значительное влияние на понимание основ и клинических проявлений психологических рас-стройств. В настоящее время известно, что новая клеточная пролиферация необходима для антиде-прессивного действия [42,[45][46][47]. Установлены факторы, регулирующие пролиферацию и нейроге-нез гиппокампальных клеток у взрослых: возраст, физическая и эмоциональная нагрузка, гормональ-ный фон, окружение и обучение.…”
Section: оригинальные статьиunclassified